Enhancement efficiency of P3HT:PCBM solar cell by different treatment annealing - Hussein, Abdullah A.; Hussain, Waleed A.; Al-luaiby, Hussein F.; Basova, Tamara; Hassan, Aseel K. (Sulaimani Journal for Pure and Applied Sciences, 2015)
Solvent Vapor Annealing (SVA) followed by Post Thermal Annealing (SVA-PA) are demonstrated as attractive methods to anneal polymer blend films and represent a very useful process to control the morphology for high performance polymer solar cells (PSCs). It is found that compared with general annealing processes, the crystallinity of regioregular poly (3-hexylthiophene) (rr-P3HT) has enhanced by performing SVA-PA on freshly deposited films. In this work we have investigated thin film blend produced from P3HT and [6,6]-phenyl-C61 butyric acid methylester (PCBM) materials. This photoactive layer is sandwiched between an anode composed of indium tin oxide (ITO)/poly(3,4 ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) gold nanoparticles (AuNPs) and Al as the cathode layer. Atomic force microscopy (AFM) study reveals that the SVA annealed films exhibit smooth surface and homogenous conductivity distribution. Moreover, an enhanced light harvesting and increased crystallinity of P3HT in the active layer are observed by UV–vis absorption and X-ray diffraction (XRD). We have seen that thermal annealing significantly improves the optical absorption ability for all treatment. We have also the current density- voltage characteristics and External quantum efficiency (EQE) of different thermal annealing.
Keywords: Solvent vapor annealingPost annealingP3HTPCBMnanoparticle